Recreational strategies for Improving English Grammar skills in the Present simple Tense for Undergraduate students - Suarez Vera, María de Jesús (Rastros Rostros, 2013)
This article presents the results of a research project using the tema-Moodle unab system to teach simple present tense grammar in English. Different activities were designed following a task-based approach (tbl) and the use of recreational strategies was also taken into account. The study sought to determine the level reached  by  A1-level  undergraduate  students  at  Universidad  Autónoma  de  Bucaramanga  (unab),  after implementing an applied recreational methodology to develop grammar skills in present simple tense. To analyze the data, the median, standard deviation and student’s  t-test were used. The sample consisted of a pilot group, a control group, and an experimental group, assigned randomly. It was found that posttest results were highest in the experimental group, with a significance level of 0.05. The improvement in grammar was due to the strategies selected, the specific way in which material was designed and organized, the direct instruction provided during the workshop, and other characteristics specific to the research project
Keywords: grammar; direct instruction; recreational methodology; present simple